Energy harvesting from flutter - Voon, Siew Li (2018)
With the continuously decreasing power requirements of modern electronics, energy harvesting from sources such as solar or wind power is becoming an increasingly viable option to power small devices almost indefinitely, without the restrictions imposed by battery replacement. In this project, a piezoelectric energy harvesting device driven by aeroelastic flutter is proposed and evaluated experimentally. From an initial harvester design, prototype harvesters are built and tested in a low-speed wind tunnel at wind speeds up to 10m/s. Three such configurations of prototypes are tested until a configuration with satisfactory performance is obtained, consisting of a cantilevered beam attached to a larger flap through a joint hinge. Based on this configuration, a parametric investigation is performed with five variables in order to study the corresponding effects on the flutter speed, output voltage, and frequency. Depending on the configuration, the prototype harvester is found to have flutter speeds of around 3m/s, above which limit cycle oscillations occur with output voltages of 10V and above. Using these results and observations, one or more parameters of the harvester can be adjusted to match a given wind environment or desired performance. Finally, potential applications of this harvester are suggested, and its performance is compared to similar harvester designs from existing literature.